A Glowing Trajectory between Bio‐ and Chemiluminescence: From Luciferin‐Based Probes to Triggerable Dioxetanes. Issue 52 (7th December 2017) - Hananya, Nir; Shabat, Doron
Abstract: Bioluminescent and chemiluminescent probes are widely used for noninvasive imaging applications because of their high sensitivity and the simplicity of the equipment required to perform the measurement. Synthetic luciferin‐analogue probes with in vivo imaging performance better than that of luciferin are now available. In addition, caged luciferin‐based bioluminogenic probes have been emerged as a general tool for the visualization of different enzymes and analytes in vivo. Recent discoveries have led to development of highly efficient chemiluminescent probes that are extremely bright under physiological conditions. As discussed in this Minireview, chemiluminescence is ready to realize its potential as a valuable tool for imaging in living systems. Abstract : Light‐emitting compounds for bioimaging : In the last decade, chemists have significantly expanded the toolbox of imaging agents by preparing new bio‐ and chemiluminescence compounds. These developments include synthetic analogues of luciferin, caged luciferin‐based bioluminogenic probes, and the recently emerging highly bright chemiluminescence dioxetane probes.